If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + 6z = 60 + -1z Combine like terms: 3z + 6z = 9z 9z = 60 + -1z Solving 9z = 60 + -1z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add 'z' to each side of the equation. 9z + z = 60 + -1z + z Combine like terms: 9z + z = 10z 10z = 60 + -1z + z Combine like terms: -1z + z = 0 10z = 60 + 0 10z = 60 Divide each side by '10'. z = 6 Simplifying z = 6
| 4+3i/5-2i | | 40p+7(1.5)p=489.85 | | 4p^2+4p-48=0 | | 6(4b-5)=23 | | (4w+3)(8+w)=0 | | 2(4t-2)+t=16t | | ((2/x)+3)=((5x-7)/x) | | 6(y-1)+5y-6=65 | | X^2+9x+6/(x+6) | | x^2+(7/2)x-2 | | 8c-3=5 | | 4+2h=10 | | 14-2(3p+1)=2(3a-2) | | 5p+3p-7=6p+21 | | (4+2)3= | | (8x-45)=(10-x/3) | | 4x^2-5x+8= | | 3(y+4)=5y+y | | 7=3+2y | | 16x^2-112x+160=0 | | 3/2x+5/2x | | 40x+120=720 | | n^2-9n+18=0 | | 1/x+2+1/x=1 | | 4x+3(2x-6y)=y | | 3g+4=10 | | 5y=3y+36 | | X^2+8x+6=13x | | 2p+2=10 | | 8a+7=7a+8a | | -7-5r=12(-9r+5) | | (7x)/(x-3)-(21)/(x-3) |